Terra nullius - Coleman, Claire G. (Sydney, NSW : Hachette Australia, 2017)
"'Jacky was running. There was no thought in his head, only an intense drive to run. There was no sense he was getting anywhere, no plan, no destination, no future. All he had was a sense of what was behind, what he was running from. Jacky was running.' The Natives of the Colony are restless. The Settlers are eager to have a nation of peace, and to bring the savages into line. Families are torn apart, reeducation is enforced. This rich land will provide for all.This is not Australia as we know it. This is not the Australia of our history. This Terra Nullius is something new, but all too familiar. An incredible debut from a striking new Australian Aboriginal voice."--Back cover.
"A novel" --Cover.
State Library of Queensland Fellowship, black&write winner 2016.
Norma K Hemming Award, winner, 2018.
Keywords: Aboriginal Australians -- Fiction; Aboriginal Australians, Treatment of -- Fiction; Colonists -- Australia -- Fiction; Law - Jurisprudence - Terra nullius; Religions - Christianity - Missions; Settlement and contacts - Colonisation; Religions - Christianity - Missionaries; Government policy - Assimilation; Australia -- Fiction; Australia -- Colonial influence -- Fiction; Australia; Australian